The caged virgin an emancipation proclamation for women and Islam - Hirsi Ali, Ayaan 1969- (Free Press, 2008)
Muslims who explore sources of morality other than Islam are threatened with death, and Muslim women who escape the virgins' cage are branded whores. So asserts Hirsi Ali's meditation on Islam and the role of women, the rights of the individual, the roots of fanaticism, and Western policies toward Islamic countries and immigrant communities. This controversial book is a call to arms for the emancipation of women from religious and cultural oppression and from an outdated cult of virginity. It is a defiant call for clear thinking and for an Islamic Enlightenment. But it is also the courageous story of how Hirsi Ali herself fought back against everyone who tried to force her to submit to a traditional Muslim woman's life and how she became a voice of reform. She relates her experiences as a Muslim woman so that oppressed Muslim women can take heart and seek their own liberation.--From publisher description.